PERTANGGUNGJAWABAN CHILD GROOMING DITINJAU DARI UNDANG-UNDANG NOMOR 19 TAHUN 2016 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Aisiyah, Andiani; Mardijono, Adianto (Gapenas Publisher, 2023)
Child Grooming means a process of approaching a child by building trust and harmony which ends in virtual sexual violence. The term Child Grooming itself emerged during the Covid-19 pandemic and over the years sexual violence against children has also increased. Sexual violence itself is regulated in Law Number 19 of 2016, Amendment to Law Number 11 of 2008 concerning Information and Electronic Transactions, however, this Law still has multiple interpretations and does not provide specific responsibilities for perpetrators of Child Grooming so that The perpetrator is still at large making children victims of sexual violence